Extraordinary concentrations of local endemism associated with arid-land springs - Fensham, Roderick J.; Ponder, Winston F.; Souza, Valeria; Stevens, Lawrence E. (Frontiers in Environmental Science, 2023)
The aim of the current study is to highlight the extraordinary endemism associated with the isolated habitat of arid-land springs. The habitat endemism of the eukaryote species associated with the aquatic and terrestrial habitats at Ash Meadows in the USA, Byarri in Australia and Cuatro Ciénegas in Mexico was assembled based on their geographic distribution. The currently-known aquatic and semi-aquatic endemic species number 27 at Ash Meadows, 31 at Byarri and 34 at Cuatro Ciénegas. Terrestrial endemic species are represented by two species at Ash Meadows, five at Byarri and 26 at Cuatro Ciénegas. The terrestrial endemics are associated with the scalded areas surrounding the springs impregnated with soda and gypsum. The persistence of the endemics is astonishing given that the wetlands represent tiny islands of habitat (216 small wetlands over 40 km2 in the case of Byarri). A key factor for the persistence and radiation of endemic species is the stability and permanence of the wetlands over evolutionary time-scales. Genetic evidence indicates the presence of both paleo-endemics, species that persisted in spring wetlands as relics of previous mesic climates; and neo-endemics that have dispersed from more mesic environments and subsequently radiated in the spring wetlands as distinct forms. The former evolved from their relatives greater than 106 ya and the latter less than 106 ya. The concentration of endemic species in and around arid-land springs is among the highest concentrations of endemic organisms specialised to a particular habitat and substantiates the paramount conservation significance of desert springs.